Research on Destination Brand Construction and Promotion-A Comparative Analysis of Guilin, China, and Santa Ana, Philippines - wang, lan (Pacific International Journal, 2024)
This research conducts a comparative analysis of destination brand construction and promotion strategies in Guilin, China, and Santa Ana, Philippines. Grounded in Destination Branding Theory and Tourist Perception and Satisfaction Theory, the study aims to unravel the strategic processes involved in crafting and managing the brand images of these distinct locations. Guilin, celebrated for its iconic karst landscapes and cultural heritage, stands as a symbol of natural beauty in China. In contrast, Santa Ana, a coastal gem in the Philippines, offers pristine beaches and marine biodiversity, positioning itself as a relatively untapped destination. The study employs a mixed-methods approach, combining in-depth interviews, surveys, and theoretical frameworks to examine the historical development, key brand components, and promotion strategies of both destinations. The findings reveal Guilin’s well- stablished brand components, emphasizing natural wonders and cultural richness, attracting visitors primarily driven by natural beauty. Santa Ana, while showcasing comparable natural beauty, relies on its cultural richness and sustainable tourism practices, positioning itself as an experiential destination. Challenges such as overcrowding and infrastructure development vary between the destinations, offering opportunities for strategic management and growth. The study concludes with tailored promotional recommendations for Guilin and Santa Ana, emphasizing the need for destination-specific strategies aligned with responsible tourism practices, ensuring a harmonious balance between growth and preservation. The research contributes nuanced insights into destination branding, providing a foundation for sustainable tourism management in diverse cultural and geographical contexts.